Nurses in China lack knowledge of inhaler devices: A cross-sectional study - Xie, Ning; Zheng, Zheng; Yang, Qilian; Li, Man; Ye, Xiaofen (Frontiers in Pharmacology, 2023)
Objective: To understand the level of knowledge about inhaler devices among medical staff. Methods: This study evaluated the knowledge of inhalation therapy and the use of inhaler devices among nurses in China. We administered a new self-designed online questionnaire to 1,831 nurses. The questionnaire comprised 11 questions, including the storage location of inhaler devices, steps involved in using inhaler devices, and common errors when using various devices. Results: Among the 1,831 participants, 816(44.57%), 122(6.66%), and 893(48.77%) nurses worked in community, secondary, and tertiary hospitals, respectively. Adequate knowledge of inhaler devices was demonstrated by 20.10%, 8.20%, and 13.10% of nurses working in community, secondary, and tertiary hospitals, respectively. Of the nurses working in community hospitals, 27.70% knew the key points for using inhalers compared to 15.57% in secondary hospitals and 23.18% in tertiary hospitals (p < 0.01). Only 9.50%–26.00% of participants chose correct answers to the 9 questions about the use of inhalers. The accuracy rate of the responses was generally low, and the highest accuracy rate was 26.00%. Conclusion: Knowledge of inhalation therapy was better among nurses working in community hospitals than among those working in high-level hospitals. This is because of the clearer division of work and higher workload in high-level hospitals. Overall, nurses’ knowledge of inhalation therapy is low. Furthermore, knowledge about inhaler devices should be strengthened among nurses in Chinese hospitals. It is necessary to create training opportunities for nurses in China to increase their awareness and knowledge regarding the management of chronic respiratory diseases.